Neurological improvement following intravenous high-dose folinic acid for cerebral folate transporter deficiency caused by FOLR-1 mutation - Delmelle, Françoise; Blau, Nenad (European journal of paediatric neurology, 2016)
Background Cerebral folate transporter deficiency caused by FOLR-1 mutations has been described in 2009. This condition is characterized by a 5MTHF level <5 nmol/l in the CSF, along with regression of acquisition in the second year of life, ataxia, and refractory myoclonic epilepsy. Oral or intravenous folinic acid (5-formyltetrahydrofolate) treatment has been shown to improve clinical status. Case presentation We present the cases of two sisters with cerebral folate transport deficiency caused by mutation in the folate receptor 1 (FOLR1) gene (MIM *136430). Following recommendations, we administered oral folinic acid at 5 mg/kg/day, resulting in some initial clinical improvement, yet severe epilepsy persisted. During treatment, cerebrospinal fluid (CSF) analysis revealed normal 5-methyltetrahydrofolate (5MTHF) levels (60.1 nmol/l; normal range: 53-182 nmol/l). Epilepsy proved difficult to control and the younger patient exhibited neurological regression. We then administered high-dose folinic acid intravenously over 3 days (6 mg/kg/day for 24 h, then 12 mg/kg/day for 48 h), which significantly improved clinical status and epilepsy. CSF analysis revealed high 5MTHF levels following intravenous infusion (180 nmol/l). Treatment continued with monthly intravenous administrations of 20-25 mg/kg folinic acid. At 2 years post-treatment, clinical improvement was confirmed. Conclusions This report illustrates that cerebral folate transporter deficiency caused by FOLR-1 mutations is a treatable condition and can potentially be cured by folinic acid treatment. As already reported, early effective treatment is known to improve outcomes in affected children. In our study, intravenous high-dose folinic acid infusions appeared to optimize clinical response.